PANDANGAN ULAMA MU’TABAR TENTANG 3 ULAMA SUFI (IBN AROBI, AL-HALLAJ DAN SYEKH SITI JENAR) - Miftahussa’adah Wardi; Muhibuddin Muhibuddin; Idrus Abidin; Lulu Masluchah; Deni Rahman; Mudrikatul Arafah; Anaway Irianti Mansyur (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi Islam Institut Agama Islam (IAI) Al-Azhaar Lubuklinggau, 2025)
This study aims to examine three major Sufi figures in the Islamic Sufi tradition, namely Ibn Arabi, Al-Hallaj, and Sheikh Siti Jenar, and the views of mu'tabar (trusted) scholars on their teachings and thoughts. This research uses a library research method with a descriptive-analytical approach. This method aims to explore in-depth the views of key figures relevant to the research topic—the views of scholars on three controversial Sufi figures: Ibn Arobi, Al-Hallaj, and Sheikh Siti Jenar. These three figures have had a significant influence on the development of Islamic mysticism, although their teachings are often seen as controversial. Ibn Arabi, with the concept of wahdat al-wujud (unity of existence), taught that everything in the universe is a manifestation of God, which can only be understood through inner search and spiritual awareness. His teachings on the unity of God and creation made a major contribution to Sufi thought, although it has been criticized by some circles because it is considered to have theological consequences that contradict mainstream Islamic teachings.